2014
DOI: 10.5539/mas.v8n4p187
|View full text |Cite
|
Sign up to set email alerts
|

Choosing Aquatic Plant Species for High Wastewater Treatment Efficiency through Small Wetland

Abstract: The research was aimed to choose the most appropriate aquatic plant in high capacity as grown in small wetland for community wastewater treatment, they were Typha angustifolia Linn., Cyperus corymbosus Rottb., and Canna indica Linn. The small wetland, sometimes called vertical flow constructed wetland (VFCW), has been designated on 100-m long, 5-m wide and 0.75-m deep in size in which four-hole pipes were laid down at the bottom for releasing some treated wastewater as effluent through the outlet to the storag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Although the two species differed significantly in terms of their total biomass, the biomass production in aboveground and underground parts did not differ. Previous studies demonstrated that the biomass yields and relative growth rates of different species of emergent plants under flooding conditions are significantly different; for example, the biomass yield of Canna is greater than that of Typha or Cyperus (Phewnil et al 2014 ). Further, higher water level or deeper burial inhibited, and more biomass was allocated to leaves at the 40 cm water level.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the two species differed significantly in terms of their total biomass, the biomass production in aboveground and underground parts did not differ. Previous studies demonstrated that the biomass yields and relative growth rates of different species of emergent plants under flooding conditions are significantly different; for example, the biomass yield of Canna is greater than that of Typha or Cyperus (Phewnil et al 2014 ). Further, higher water level or deeper burial inhibited, and more biomass was allocated to leaves at the 40 cm water level.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, household wastewater is contaminated with organic substances. The pollutants in municipal wastewater (MW) can be mainly characterized by the biochemical oxygen demand (BOD), chemical oxygen demand (COD), total nitrogen (TN), ammonium nitrogen (NH 4 -N), and total phosphorus (TP) (Chunkao et al 2012 ; Phewnil et al 2014 ). Phetchaburi Municipality is in Phetchaburi Province, Thailand, around 150 km from Bangkok, Thailand.…”
Section: Introductionmentioning
confidence: 99%
“…Typha colonizes a large surface area and produces very high biomass yield [44]. C. indica is considered a phytoremediation plant, with a flourishing root system with higher root growth, higher root number, larger root biomass, and significantly larger root surface area than other plant species [45].…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%
“…The indicated that average growth rate was more or less zero when their ages reached at about 90 days and 45 days for useful life of Typha and Cyperus, respectively. The aforesaid statement presented that Typha and Cyperus grew well in Phetchaburi municipal wastewater and also the maximum effective treatment in constructed wetland concept., although Typha was high evapotranspiration rate (Pedescoll et al, 2013;Phewnil et al, 2014) …”
Section: Biomass and Accumulative Plant Nutrientsmentioning
confidence: 99%